Design of Workshop Control System Based on Digital Twin. Issue 1 (1st December 2022) - Zheng, Liang; Yuan, Minghai; Pei, Fengque; Mao, Kefu
Abstract: For the problems of the traditional workshop control system, such as closed information and untimely delivery, the web-based digital twin workshop control system is designed from the concept of the digital twin. According to the physical entities in the workshop, the corresponding digital twin model is constructed, and the design of the whole process, from the collection of workshop data to the application, is completed. Finally, the system is applied to a small workshop, and the results show that the digital twin-based workshop control system could significantly improve the workshop's productivity.